Biomass-to-Green Hydrogen: A Review of Techno-Economic-Enviro Assessment of Various Production Methods - Ghasemi, Amir; Nikafshan Rad, Hima; Akrami, Mohammad (Hydrogen, 2024)
H2 is considered a practical substitute for fossil fuels, especially for transportation by road and air, created either from fossil fuels or through the process of electrolysis of water. Research questions were included based on numerous research and the analysis of articles. The cost analysis of H2 processes, techno-economic hurdles in commercialization, and the economic comparison of various H2-production methods were the basis for the study of papers. The current research examines the different methods of thermochemical, biological, and electrochemical processes utilized in converting biomass into hydrogen. The benefits, constraints, and significant enhancements of every procedure are outlined. The examination assesses the cost of production, the level of technology readiness, and the potential for scalability. Thermochemical techniques, such as gasification and steam reforming, are effective at producing hydrogen. Steam gasification is perfect for moist and dry biomass in the absence of an oxidizing agent. Dark fermentation is more efficient for biological conversion because it requires less energy. Moreover, the electrochemical procedure is viable for biomass. Thermochemical treatment is significantly more advanced than biological or electrochemical treatment when it comes to scaling opportunities based on comparisons of current processes. The results of this research show that biomass–hydrogen processes have the potential for increasing H2 production, but further enhancements are needed to produce larger quantities for competitiveness.